Repulsive/Attractive Discrete State Space Sets for Switching Management - Kamach, 0ulaid; Niel, Eric; Piétrac, Laurent (Studies in Informatics and Control, 2007)
This paper deals with operating mode management of Discrete Event Systems (DES) and this contribution is based on Supervisory Control Theory (SCT). Our aim is to extend SCT by introducing a mechanism for managing different operating modes for the controlled system. An operating mode corresponds to a specific system structure (engagement or disengagement of different system components) and specified tasks. Mode management will consist in controlling switching between modes with a view to handling models of reasonable size. Our approach is a multi-model one and involves representing a complex system by a set of simple models, each of which describes the system in a given operating mode. The adopted approach assumes that only one attempted operating mode is activated at a time, whilst other modes must be deactivated. The switching problem may be defined as finding compatible states, when controlled system behavior switches from one operating mode to another. The major contribution of this paper is the avoidance of switching from states (called forbidden states) with ghost compatible states in the selected operating mode. These states are called ghost because their existence would potentially violate a defined selected mode specification.